Collagen I in the Hip Capsule Plays a Role in Postoperative Clinical Function in Patients With Developmental Dysplasia of the Hip - Zhang, Sicheng; Song, Jun; Wu, Qingjie; Fang, Jihong; Ning, Bo (Frontiers in Pediatrics, 2022)
The aims of the present study is to evaluate the roles of collagen I and III in the hip capsule in the postoperative clinical function of patients with developmental dysplasia of the hip (DDH). Hip capsules from 155 hips of 120 patients were collected during surgery. The patients were divided into three groups according to age: I: 2–3.5 years; II: 3.5–5 years; and III: 5–6 years. Patient clinical function and radiographic outcomes were evaluated with the McKay scores and Severin classification. The expression of collagen I and III was detected through immunohistochemistry and quantitative reverse transcription polymerase chain reaction (RT-PCR) and analysed according to age, sex, degree of dislocation and McKay classification. All patients received open reduction and pelvic osteotomy and/or femoral shortening osteotomy and achieved good results on the basis of postoperative X-ray imaging. The average follow-up time was 3.4 years (range 2–4.3 years). There were no changes in the expression of collagen III in the different groups. The expression of collagen I according to age and sex was not significantly different. Lower expression of collagen I was observed in DDH patients with a higher degree of dislocation according to the Tonnis grade. The highest expression of collagen I was detected in the group with poor clinical function according to the McKay classification. Collagen I is correlated with the degree of dislocation and is a risk factor for poor clinical function in DDH patients. Collagen I is correlated with the degree of hip dislocation and poor clinical function in DDH patients.